Soybean production pointers in Rio Grande do Sul compared to the agricultural zoning - Melo, Ricardo Wanke de; Fontana, Denise Cybis; Berlato, Moacir Antonio (Pesquisa Agropecuaria Brasileira, 2004)
The State of Rio Grande do Sul is responsible for approximately 20% of the national soybean production. For this reason better knowledge about pointers of this crop production in this State becomes necessary. The objective of this work was to analyse, comparing to the agricultural zoning, some soybean production pointers in the counties that are part of the signicant production region of this crop in Rio Grande do Sul. The grouping analysis was carried by the Ward’s method. Counties were grouped according to the yield, the production and the ratio of the soybean harvested area and the total county area. The yield grouping analysis result was compared to the soybean agroclimatic zoning for the State. There is narrow relation among the groups formed by the three variables analysis. The soybean agroclimatic zoning in the State of Rio Grande do Sul presents a possible inconsistency in the grouping of the counties by yield. In the other groupings, this inconsistency is not observed.